Self-healing and mechanical performance of dynamic glycol chitosan hydrogel nanocomposites. Issue 3 (18th December 2020) - Efstathiou, Spyridon; Wemyss, Alan M.; Patias, Georgios; Al-Shok, Lucas; Grypioti, Maria; Coursari, Despina; Ma, Congkai; Atkins, Christophe J.; Shegiwal, Ataulla; Wan, Chaoying; Haddleton, David M.
Abstract : Evaluation of Schiff base nanocomposite hydrogels properties using a benzaldehyde multifunctional amphiphilic polyacrylamide crosslinker in conjunction with glycol chitosan. Abstract : The application of functional self-healing and mechanically robust hydrogels in bioengineering, drug delivery, soft robotics, etc., is continuously growing. However, fabricating hydrogels that simultaneously possess good mechanical and self-healing properties remains a challenge. Developing robust hydrogel formulations for the encapsulation and release of hydrophobic substances is a major challenge especially in some pharmaceutical treatments where the many of drugs show incompatibility with the hydrophilic hydrogel matrices. Schiff base hydrogels have been developed using a benzaldehyde multifunctional amphiphilic polyacrylamide crosslinker in conjunction with glycol chitosan. The polymeric crosslinker was synthesized by a two-step reaction using aqueous Cu-RDRP to give an ABA telechelic copolymer of N, N -dimethyl acrylamide (DMAc) and N -hydroxyethyl acrylamide (HEAm) from a bifunctional PEG. The polymer was then modified by post functionalization leading to a multifunctional benzaldehyde crosslinker that was shown to be capable of self-assembly into aggregates in aqueous media serving as a possible candidate for the entrapment of hydrophobic substances. Aqueous solutions of the crosslinker spontaneously formed hydrogels when mixed with glycol chitosan due to the in situ formation of imine bonds. Hydrogels were characterized while additional comparisons were made with a commonly used bifunctional PEG crosslinker. The effect of introducing partially reduced graphene oxide (GO) nanosheets was also examined and led to enhancements in both mechanical properties (2.0 fold increase in modulus and 1.4 fold increase in strain) and self-healing efficiencies (>99% from 60% by rheology) relative to the pristine polymer hydrogels.